2021
DOI: 10.3390/molecules26144221
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Testing of Radiopharmaceuticals for the Detection and Characterization of Osteomyelitis: Experiences from a Porcine Model

Abstract: The development of new and better radioactive tracers capable of detecting and characterizing osteomyelitis is an ongoing process, mainly because available tracers lack selectivity towards osteomyelitis. An integrated part of developing new tracers is the performance of in vivo tests using appropriate animal models. The available animal models for osteomyelitis are also far from ideal. Therefore, developing improved animal osteomyelitis models is as important as developing new radioactive tracers. We recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, to successfully provide valid pre-clinical data for clinical translation, the animal model should be standardized and reflect the pathogenesis of infectious disease in humans. Thus, further harmonizing the design and animal study requirements is recommended. , Furthermore, it should be considered that targeting bacteria with low metabolic activity will probably not render sufficient tracer “load” to allow for its visualization. Therefore, the correct window to employ imaging to detect or monitor infection should be considered .…”
Section: Design Approach and Challenges For Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to successfully provide valid pre-clinical data for clinical translation, the animal model should be standardized and reflect the pathogenesis of infectious disease in humans. Thus, further harmonizing the design and animal study requirements is recommended. , Furthermore, it should be considered that targeting bacteria with low metabolic activity will probably not render sufficient tracer “load” to allow for its visualization. Therefore, the correct window to employ imaging to detect or monitor infection should be considered .…”
Section: Design Approach and Challenges For Translationmentioning
confidence: 99%
“…However, small radiolabeled molecules with high selectivity and specificity for bacteria emerged with great potential as precise agents for non-invasive infection imaging. Despite that, their clinical translation has been limited by access and suitability to appropriate animal infection models as well as the study design that is allowed based on animal pathology or well-being. The variability in the choice of animal model and study design has been observed across different studies, which might pose a challenge to data interpretation and reproducibility. For example, a previous study reported bacterial uptake of [ 3 H]- l -Met using lung infection models which was not observed in a study using a murine myositis model. , This inconsistency could be due to a number of factors, including the use of different bacterial strains, the number of colonies inoculated, the type of animal infection model, or the imaging time points chosen during the course of infection.…”
Section: Design Approach and Challenges For Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…In HO research, various inoculum routes have been utilized, including arterial (brachial [ 248 ] or femoral [ 252 ] artery), intravenous (ear vein [ 253 ]) and traumatic approaches [ 245 ] ( Fig. 4 c).…”
Section: Homentioning
confidence: 99%